Experimental application of a laser‐based manufacturing process to develop a free customizable, scalable thermoelectric generator demonstrated on a hot shaft. Issue 4 (13th November 2022) - Abt, Marvin; Kruppa, Katharina; Wolf, Mario; Feldhoff, Armin; Overmeyer, Ludger
Abstract: Geometry, design, and processing in addition to the thermoelectric material properties have a significant influence on the economic efficiency and performance of thermoelectric generators (TEGs). While conventional BULK TEGs are elaborate to manufacture and allow only limited variations in geometry, printed TEGs are often restricted in their application and processing temperature due to the use of organic materials. In this work, a proof‐of‐concept for fabricating modular, customizable, and temperature‐stable TEGs is demonstrated by applying an alternative laser process. For this purpose, low temperature cofired ceramics substrates were coated over a large area, freely structured and cut without masks by a laser and sintered to a solid structure in a single optimized thermal post‐processing. A scalable design with complex geometry and large cooling surface for application on a hot shaft was realized to prove feasibility. Investigations on sintering characteristics up to a peak temperature of 1173 K, thermoelectric material properties and temperature distribution were carried out for a Ca3 Co4 O9 /Ag‐based prototype and evaluated using profilometer, XRD, and IR measurements. For a combined post‐processing, an optimal sintering profile could be determined at 1073 K peak temperature with a 20 min holding time. Temperature gradients of up to 100 K could be achieved along a thermocouple. A single TEG module consisting of 12 thermocouples achieved a maximum power of 0.224 μW and open‐circuit voltage of 134.41 mV at an average hot‐side temperature of 413.6 K and temperature difference of 106.7 K. Three of these modules combined into a common TEG with a total of 36 thermocouples reached a maximum power of 0.58 K and open‐circuit voltage of 319.28 mV with a lesser average hot‐side temperature of 387.8 K and temperature difference of 83.4 K. Abstract : Modular, customizable, and thermal stable. Geometry and design of a thermoelectric generator (TEG) have significant influence on its performance. This work shows how low temperature cofired ceramics technology and laser structuring can be combined for flexible manufacturing of TEG with a high level of geometric freedom. A CCO/Ag based generator is manufactured from several modules. Characterization of sintering profiles, temperature distributions, materials, and TEG performance are carried out.